2018
DOI: 10.1161/jaha.117.007584
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a History of Hypertension in Pregnancy on Later Diagnosis of Atrial Fibrillation

Abstract: BackgroundAtrial fibrillation/flutter (AF) produces significant morbidity in women and is typically attributed to cardiac remodeling from multiple causes, particularly hypertension. Hypertensive pregnancy disorders (HPDs) are associated with future hypertension and adverse cardiac remodeling. We evaluated whether women with AF were more likely to have experienced a HPD compared with those without.Methods and ResultsA nested case–control study was conducted within a cohort of 7566 women who had a live or stillb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 28 publications
(49 reference statements)
0
27
0
2
Order By: Relevance
“…A recent nested case-control study from Olmsted County, Minnesota, reported women with AF to be more likely to have experienced a hypertensive pregnancy disorder. This relationship was at least partially mediated by associated obesity and hypertension (54).…”
Section: Hypertensive Disorders Of Pregnancymentioning
confidence: 98%
“…A recent nested case-control study from Olmsted County, Minnesota, reported women with AF to be more likely to have experienced a hypertensive pregnancy disorder. This relationship was at least partially mediated by associated obesity and hypertension (54).…”
Section: Hypertensive Disorders Of Pregnancymentioning
confidence: 98%
“…An aspect of CVD risk that has not been previously examined is the relationship between HDP and atrial fibrillation, which is explored by Scantlebury et al in a recent issue of the Journal of the American Heart Association (JAHA) 53. In a nested case–control study conducted within a cohort of >7000 women, 105 cases of atrial fibrillation were compared with 105 controls.…”
Section: Hdp and Long‐term Risk Of Maternal Cvdmentioning
confidence: 99%
“…While gestational hypertension, gestational diabetes, and preeclampsia are independently associated with the long-term development of cardiovascular disease [ 14 , 15 ], the association between these pregnancy complications and incident risk of atrial fibrillation has not been well-studied. Olmstead county data showed that hypertensive disease in pregnancy predicts the development of atrial fibrillation later in life with an odds ratio of 2.6, but this association was attenuated and not statistically significant (OR 2.12, confidence interval 0.92-5.23), when adjusted for hypertension and obesity [ 16 ].…”
Section: Introductionmentioning
confidence: 99%